The Effects of Selenium Supplementation on Glucose Metabolism and Lipid Profiles Among Patients with Metabolic Diseases: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Tabrizi, Reza; Akbari, Maryam; Moosazadeh, Mahmood; Lankarani, Kamran B.; Heydari, Seyed Taghi; Kolahdooz, Fariba; Mohammadi, Ali Akbar; Shabani, Azade; Badehnoosh, Bita; Jamilian, Mehri; Assarian, Amin; Asemi, Zatollah (Hormone and Metabolic Research, 2017)
This systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to summarize the effect of selenium administration on glucose metabolism and lipid profiles among patients with diseases related to metabolic syndrome (MetS). We searched the following databases up to May 2017: MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials. The relevant data were extracted and assessed for quality of the studies according to the Cochrane risk of bias tool. Data were pooled using the inverse variance method and expressed as standardized mean difference (MDs) with 95% confidence intervals (95% CI). Five studies were included in the meta-analyses. The results showed that selenium supplementation significantly reduced insulin levels (SMD −0.42; 95% CI, −0.83 to −0.01) and increased quantitative insulin sensitivity check index (QUICKI) (SMD 0.83; 95% CI, 0.58 to 1.09). Selenium supplementation had no beneficial effects on other glucose homeostasis parameters, such as fasting plasma glucose (FPG) (SMD −0.29; 95% CI, −0.73 to 0.15), homeostasis model assessment of insulin resistance (HOMA-IR) (SMD −0.80; 95% CI, −1.58 to −0.03), and lipid profiles, such as triglycerides (SMD −0.42; 95% CI, −0.83 to −0.01), VLDL- (SMD −0.42; 95% CI, −0.83 to −0.01), total- (SMD −0.42; 95% CI, −0.83 to −0.01), LDL- (SMD 0.02; 95% CI, −0.20 to 0.24), and HDL-cholesterol (SMD 0.16; 95% CI, −0.06 to −0.38). Overall, this meta-analysis showed that selenium administration may lead to an improvement in insulin and QUICKI, but did not affect FPG, HOMA-IR, and lipid profiles.
Keywords: selenium; glucose homeostasis; lipid profiles; meta-analysis